Determinants of household's modern cooking and lighting energy transition in rural India: Exploring household's activities and its interactions with other households - Varun Gaur (University of Bonn, Center for Development Research (ZEF), 2018)
The majority of rural Indian households remain dependent on unreliable, inefficient and harmful household energy technologies. Rural households make their energy decisions with respect to the Water-Energy-Food security (WEF) Nexus jointly, however, previous research initiatives have analyzed household energy access problem in isolation. By analyzing household's activities and its interactions with other households, this paper identified the factors that impact household's transition to modern energies of different kinds. For the analysis, it utilized logit and zoib (zero-one-inflated beta) regression techniques on the household survey data set from the Uttar Pradesh province of India. The results showed that regular non-agricultural income of household's male member increases the probability of household's modern cooking energy and modern lighting transition by 8.6% and 13.6%, respectively. It was found that household's higher agricultural dependence and resource endowments (more labor and cattle) lead to higher share of traditional bioenergy consumption in the total cooking energy mix. Proximity to markets and high household income were observed to positively influence household modern cooking and lighting transition. Local institutions such as local bio-energy markets and barter trade for labor-bioenergy was observed to have significant influence on household energy choice. Results also showed that government's policy instrument such as household connection to government LPG scheme is associated with 20.5% increased probability of household using modern cooking energy as its primary cooking fuel. Results also indicated that social factors such as higher female education and young age of household head are associated with household's increased modern cooking energy consumption in its total cooking energy mix.
Keywords: 330; Nexus; Determinants; Energy use; ZOIB; Logit